(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Renewable energy source, wind energy has enormous potential it offers not only a viablealternative to traditional fossil fuels, but also promising early indicators of being able to mitigate negativeenvironmental impacts. There is a tremendous energy potential from offshore wind. For offshore windfarms in deeper water, (FOWT) is an option. The use of wind power in the energy sector has increasedintensely over the past two decades. The indigenous wind power industry in India has been at theforefront of the country’s renewable energy revolution. A vibrant ecosystem, project operatingcapabilities, or manufacturing base of around 12000MW per annum have emerged from the growth of thewind industry. A clean indigenous source of power for the people of India may come in the form ofwind power, which has quickly become one of the country’s most significant sources of renewableenergy for energy production.